Falsely elevated serum testosterone measurements resulting from testosterone topical gel contamination of the venipuncture site: Case Series and retrospective review - Aranza Pinedo Pichilingue; Dina N. Greene; Matthew D. Krasowski (Heliyon, 2023)
Testosterone as replacement therapy for male hypogonadism or as gender-affirming hormone therapy for transgender and non-binary patients has increased worldwide. Commonly used formulations of testosterone include intramuscular, transdermal patch, and topical gel, each of which has differing pharmacokinetics and practical challenges. In monitoring testosterone serum concentrations, contamination of the phlebotomy site by testosterone topical gel can lead to supraphysiologic (>1000 ng/dL or 34.7 nmol/L) serum concentrations of testosterone, as demonstrated in a few published case reports. The frequency of this issue is currently not known. The present study involves a retrospective search over a 13-year period across all clinical sites at an academic medical center. Out of 578 unique patients using testosterone topical gel, a total of 48 patients had at least 1 testosterone serum concentration exceed 1000 ng/dL. Documentation in the electronic health record revealed 7 patients where contamination of the phlebotomy site by topical gel was strongly supported as the cause of supraphysiologic testosterone serum concentrations. These included 5 males with primary hypogonadism, 1 male with panhypopituitarism, and a non-binary patient with gender dysphoria. The high testosterone concentrations prompted further work-up, including retesting and endocrinology consultation. There were additional cases of high testosterone serum concentration that may have been falsely elevated due to gel contamination but without sufficient supporting evidence available in the health record. Overall, we present 7 cases of spuriously high testosterone concentrations strongly suspected to be due to venipuncture performed near or at the location of prior testosterone gel application. Gel contamination should be considered as a possible cause of otherwise unexplained high testosterone serum concentration in patients receiving topical testosterone gel formulations. Patient counseling and provider awareness of this potential cause of spuriously high testosterone serum concentrations is important.